Pentingnya Sosialisasi Keselamatan dan Kesehatan Kerja (K3) Di Lingkungan Padat Penduduk - Sari, Wedha; Nanang Ruhyat (LP3M Universitas Putra Bangsa, 2024)
Socialization of Occupational Safety and Health (K3) in densely populated settlements has high urgency considering that densely populated settlements often face high risks related to safety and health. By actively involving the community, this outreach program aims to establish a strong safety culture and create a safer and healthier environment. The urgency lies in the need to overcome problems such as fires, evacuation access and unavailability of extinguishers which pose risks in densely populated settlements. With proper K3 outreach, community preparedness can be increased for fires, natural disasters and so on. The program's objectives include increasing community knowledge about OSH practices, changing positive attitudes towards safety, and adopting safer behavior. Apart from that, establishing a local K3 volunteer team is also a strategic goal to ensure continuity and dissemination of information at the community level. The targeted output involves active community participation in training and outreach. It is hoped that the formation of an K3 volunteer team, a significant increase in community knowledge after socialization, as well as positive changes in attitudes and behavior regarding K3.